MRI-Based Radiotherapy Planning to Reduce Rectal Dose in Excess of Tolerance. (3rd February 2022) - Schmidt, Daniel R.; Bhagwat, Mandar; Glazer, Daniel I.; Chen, Ming-Hui; Moteabbed, Maryam; McMahon, Elizabeth; Loffredo, Marian J.; Tempany, Clare M.; D'Amico, Anthony V.
Abstract : Background and Purpose . Chronic rectal toxicity significantly decreases the quality of life for men who receive radiotherapy for prostate cancer. The most significant predictor of rectal toxicity is rectal dose-volume exceeding tolerance. To minimize the volume of rectum in the high dose field, it is essential to accurately define the prostate-rectum interface. This can be challenging to do by computed tomography (CT) imaging alone. The current study was undertaken to formally demonstrate in a clinical trial setting that image-guided intensity-modulated radiation therapy (IG-IMRT) planning using magnetic resonance imaging (MRI) can reduce the volume of rectum exceeding 70 Gy, a validated metric that predicts the risk of late rectal toxicity. Materials and Methods. This prospective single-arm study enrolled 15 men treated with IG-IMRT for localized prostate cancer. All participants received a dedicated 3 Tesla MRI examination of the prostate in addition to a pelvic CT examination for treatment planning. Two volumetric modulated arc therapy (VMAT) plans with a prescription dose of 79.2 Gy were designed using identical constraints based on CT- and MRI-defined consensus volumes. The volume of rectum exposed to 70 Gy or more was compared using the Wilcoxon paired signed rank test. Results . For CT-based treatment plans, the median volume of rectum receiving 70 Gy or more was 9.3 cubic centimeters (cc) (IQR 7.0 to 10.2) compared with 4.9 cc (IQR 4.1 to 7.8) for MRI-based plans. This resulted in a median volume reduction of 2.1 cc (IQR 0.5 to 5.3, P < .001). Conclusions . Using MRI to plan prostate IG-IMRT to a dose of 79.2 Gy reduces the volume of rectum receiving radiation dose in excess of tolerance (70 Gy or more) and should be considered in men who are at high risk for late rectal toxicity and are not good candidates for other rectal sparing techniques such as hydrogel spacer. This trial is registered with NCT02470910 .